Predicting Metapopulation Responses to Conservation in Human-Dominated Landscapes - Ladin, Zachary S.; D'Amico, Vincent; Baetens, Jan M.; Roth, Roland R.; Shriver, W. Gregory (Frontiers in Ecology and Evolution, 2016)
Loss of habitat to urbanization is a primary cause of population declines as human-dominated landscapes expand at increasing rates. Understanding how the relative effects of different conservation strategies is important to slow population declines for species in urban landscapes. We studied the wood thrush Hylocichla mustelina, a declining forest-breeding Neotropical migratory species, and umbrella species for forest-breeding songbirds, within the urbanized mid-Atlantic United States. We integrated 40 years of demographic data with contemporary metapopulation model simulations of breeding wood thrushes to predict population responses to differing conservation scenarios. We compared four conservation scenarios over a 30-year time period (2014–2044) representing A) current observed state (Null), B) replacing impervious surface with forest (Reforest), C) reducing brown-headed cowbird Molothrus ater parasitism pressure (Cowbird removal), and D) simultaneous reforesting and cowbird removal. Compared to the Null scenario, the Reforest scenario increased mean annual population trends by 54 % , the Remove cowbirds scenario increased mean annual population trends by 38 %, and the scenario combining reforestation and cowbird removal increased mean annual population trends by 98 %. Mean annual growth rates (λ) per site were greater in the Reforest (λ = 0.94) and Remove cowbirds (λ = 0.92) compared to the Null (λ = 0.88) model scenarios. However, only by combining the positive effects of reforestation and cowbird removal did wood thrush populations stop declining (λ = 1.00). Our results suggest that independently replacing impervious surface with forest habitat around forest patches and removing cowbirds may slow current negative population trends. Furthermore, conservation efforts that combine reforestation and cowbird removal may potentially benefit populations of wood thrushes and other similarly forest-breeding songbird species within urbanized fragmented landscapes that typify the mid-Atlantic United States.